THE CAPACITY AND CIRCULATION OF PASSENGER TERMINAL BUILDING IN REGIONAL AIRPORT (CASE: MINANGKABAU AND ADISUTJIPTO INTERNATIONAL AIRPORTS OF INDONESIA) - Amalia Defiani (Department of Civil and Environmental Engineering, Faculty of Engineering, UGM, 2012)
The dissertation explains about capacity and flow inside terminal buildings in two regional airports in Indonesia: Minangkabau and Adisutjipto International Airports. Both airports have similar characteristics of passengers’ number and locations as tourism areas. Secondary data in the form of existing terminal layouts and air traffic numbers were gained from both airports authorities in Indonesia. The analysis was carried out using the formulas from Japan International Cooperation Agency – Directorate General of Civil Aviation of Indonesia(JICA-DGCA) studies in 1996 for significant areas in the terminal building, Ashford and Wright formula for calculating aircraft movement per hour, Microsoft Excel for calculating the 10-year passenger growth rate, and SPSS for determining the linear equation for domestic departure resulted in the forecasted saturation in the near 2020 for both of airports, especially on passengers’ handling areas such as boarding lounge (for departure) and baggage claim area (for arrival). The research resulted in ideas to overcome problems related to the increasing capacity by adding areas (if possible) and changing layouts. Some other options such as implementation of more effective signage and the suggestion of centralizing security checking areas also are being brought—though needed further research. There should be an addition of numbers of security check lines, appropriately to the increasing number of passengers. If a single queuing line creates delays, then the need for extra line(s) is a necessity Keywords: Airport, Terminal Building, Capacity, Flow, Minangkabau, Adisutjipto